2020
DOI: 10.1097/scs.0000000000006493
|View full text |Cite
|
Sign up to set email alerts
|

Modified Endoscopic Dacryocystorhinostomy Using the Middle Uncinate Process Approach

Abstract: Purpose: Endoscopic dacryocystorhinostomy (EDCR) is advantageous in that it avoids facial scar formation, does not damage the medial canthus ligament, and recovers quickly. The main purpose of EDCR is to establish a fistula large enough to completely expose the lacrimal sac and avoid complications. Accurate location of lacrimal sac and complete opening of lacrimal sac are the keys to successful operation. However, due to the individual differences in the size of the lacrimal sac and the anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…[7] The key to successful DCR is believed to be proper identi cation of the LS and its complete exposure and opening. [10] Considering the anatomic relationships of the LS with the internal surface of the nasal cavity, the upper boundary of the LS -and, consequently, most of the LS itself -is located above the level of the axilla of the middle turbinate. This anatomic landmark helps explain the need for a higher placement of the incision and subsequent ap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] The key to successful DCR is believed to be proper identi cation of the LS and its complete exposure and opening. [10] Considering the anatomic relationships of the LS with the internal surface of the nasal cavity, the upper boundary of the LS -and, consequently, most of the LS itself -is located above the level of the axilla of the middle turbinate. This anatomic landmark helps explain the need for a higher placement of the incision and subsequent ap.…”
Section: Discussionmentioning
confidence: 99%
“…[6-8] It is critical that surgeons who intend to perform endoscopic DCR understand the anatomy of the lateral nasal wall and its landmarks -such as the anterior region of the uncinate process, the axilla of the middle turbinate, the agger nasi cell, and the "lacrimal bulge" -to ensure proper identi cation and opening of the LS. [6, [9][10][11] The LS has a close relationship with the agger nasi; indeed, this ethmoidal air cell makes up the posteromedial boundary of the LS. [9,12] In a study published by Remor et al regarding this association, CT evaluation of the relationship between the AN and the LS revealed that, in almost 60% of cases, the most anterior ethmoidal cell is located medial to the LS; its anterior opening can thus be inferred to constitute an important step for proper LS exposure and postoperative control.…”
Section: Introductionmentioning
confidence: 99%
“…En-DCRs were performed to patients with NLDO, chronic dacryocystitis, acute dacryocystitis, dacryocyst mucoceles or traumatic dacryocystitis. The surgeries were conducted with a standard process depicted in former reports [4][5][6]11] . In many cases, silicone tubes were not implanted, except for punctual stenosis, canalicular stenosis, lacrimal sac scarring, or upper nasal cavity narrow.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…Outcome success can be evaluated using anatomic and/or functional methods. Almost all the articles showed differences in anatomical and functional success rates, with functional success rates consistently slightly lower than anatomical success rates [5][6] . This means that in certain situations, patients grumble of troublesome epiphora even though lacrimal duct is patent by lacrimal irrigation test and endoscopic examination, and the situation is named "functional epiphora" after En-DCR [6][7][8] .…”
Section: Introductionmentioning
confidence: 94%
“…Під час ендоназальної мікроендоскопічної дакріоцисториностомії «тонка як папір» сльозова кістка виступає в ролі «хірургічного вікна» і використовується для доступу до слізного мішка [25]. Отже, нижня частина слізного мішка й верхня частина слізної протоки можуть бути легко доступними зсередини носа, що допомагає уникнути як зовнішнього, так і внутрішнього доступу через щільний лобовий відросток верхньої щелепи, які зазвичай залишають незадовільний косметичний дефект і характеризується більш тривалим загоєнням рани [26,27]. Первинне скостеніння сльозової кістки з'являється на третьому місяці внутрішньоутробного розвитку.…”
unclassified